Social Justice, Cultures of Peace and Digital Competences: Communication for Critical Global Citizenship in Higher Education - Eloísa Nos Aldás; Alessandra Farné; Tamer Al-Najjar Trujillo (Universidad Autónoma de Madrid, 2019)
This paper presents a revision of the theoretical grounding, implementation and evaluation of a proposal of critical learning based on values of peace, equality and global social justice. The article addresses the case of transgressive communication of social change in higher education through participatory and cooperative methodologies to acquire communicative and digital competences in the context of the Sustainable Development Goals. In addition, we address the main educational challenges in the university context considering the role played by the digital social media in the learning process and the configuration of identities. Specifically, we analyse two courses of the Universitat Jaume I of Castellón (Spain): "Communication towards equality", in the undergraduate in Advertising and Public Relations, and "Communication for peace", of the Master in International Studies in Peace, Conflict and Development. These proposals are grounded on a conception of higher education as a learning and communicative community as critical and active citizens able to trace the root causes of cultural violence in order to imagine and promote other realities, by creating alternative discourses. We rely on critical pedagogy and transgressive communication of social change to focus on detect successful transformative discourses to learn how to build other political options through communication.